CHRONIC HEART FAILURE AND IRON-DEFICIENT ANEMIA - M. V. Melnik; A. M. Shilov; I. R. Kim; O. N. Retivykh; A. A. Saricheva (Рациональная фармакотерапия в кардиологии, 2015)
62 chronic heart failure (CHF) patients with iron-deficient anemia (IDA) were studied. Standard CHF therapy (angiotensin converting enzyme inhibitors, β-blockers, diuretics, cardiac glycosides) was accompanied with the correction of iron deficiency by intravenous injection of Venofer and subsequent Ferro-Folgamma prescription (average daily dose of iron 137,75±5mg). After treatment serum iron level increased by 95,5% and hemoglobin level – by 9,8%. Left ventricular ejection fraction increased by 32,2% and physical activity tolerance – by 47,6%. Before treatment 32 CHF patients with IDA (51,6%) had III functional class (FC) of CHF according to NYHA and 16 patients (25,8%) – IV FC. After treatment I FC was observed in 18 CHF patients (29%), II FC – in 26 patients and only 18 patients demonstrated III FC of CHF.